AB0285 RANDOMIZED, OPEN-LABEL, SINGLE-DOSE, PARALLEL-GROUP PHARMACOKINETIC STUDY OF PF-06410293, AN ADALIMUMAB BIOSIMILAR, BY SUBCUTANEOUS DOSING USING A PREFILLED SYRINGE OR A PREFILLED PEN IN HEALTHY SUBJECTS. (2nd June 2020) - Cox, D.; Alvarez, D.; Bock, A.; Cronenberger, C.
Abstract : Background: Similarity in efficacy, safety, and immunogenicity (IMG) of PF-06410293 (ADL-PF), an adalimumab (ADL) biosimilar, and reference ADL sourced from the European Union (ADL-EU), by subcutaneous (SC) injection using a prefilled syringe (PFS), have been demonstrated in a randomised controlled trial in patients with rheumatoid arthritis (RA) (NCT02480153 ). Objectives: To determine if the pharmacokinetics (PK), safety and tolerability of ADL-PF were similar following a single SC dose by prefilled pen (PFP) or PFS in healthy subjects (NCT02572245 ). Methods: In this phase 1, 2-arm study, healthy subjects, aged 18–55 years, were randomised (1:1) to receive ADL-PF (40 mg, SC) in the lower abdomen or upper anterior thigh by PFS or PFP. Primary endpoints were maximum observed serum concentration (Cmax ) and area under the serum concentration–time profile from time 0–2 weeks after dosing (AUC0-2wk ). Safety, including injection-site reactions (ISRs), and secondary PK endpoints, were also assessed. Bioequivalence between ADL-PF administered by PFS or PFP device was demonstrated if the 90% confidence intervals (CIs) for the test/reference ratios of AUC0-2wk and Cmax fell within the 80.00–125.00% pre-specified margin. Results: A total of 164 subjects, stratified by body weight were randomised and assigned to treatment; ADL-PF PFS (n=81) and PFP (n=83). Baseline characteristics were comparable between treatment arms. 163 subjects were included in the primary PK analysis. The concentration–time profiles were comparable between the ADL-PF PFS and PFP treatment arms, and were characterized by an increase in serum drug concentrations, with the Cmax achieved at approximately 6-7 days, followed by a multi-phasic decline in drug concentrations. The 90% CIs for test/reference ratios of the geometric means for the primary PK parameters fell within the pre-specified margin (Table ). In total, 50 and 51 treatment-emergent adverse events (AEs) were reported in 31 (38.3%) and 29 subjects (34.9%), respectively, in the ADL-PF PFS and PFP groups. One subject experienced an unrelated serious AE in the ADL-PF PFS group. Injection-site pain was similar between treatment arms at all time points, and for the 2 injection-site locations. IMG testing was limited to subjects experiencing an ISR and/or rash AE, and a matched control group, with 11 (11/15; 73.3%) and 7 (7/15; 46.7%) subjects, respectively, testing anti-drug antibody (ADA)-positive. Amongst ADA-positive subjects, a majority (12/18) also tested positive for neutralising ADAs (7/11 [63.6%] and 5/7 [71.4%] subjects, respectively). Conclusion: This study demonstrated that the PK of ADL-PF was comparable following SC administration using either a PFS or PFP device. ADL-PF by PFS or PFP injection was well tolerated by healthy subjects, with the distribution of AEs, including ISRs, being similar between treatment arms. Acknowledgments: Medical writing support was provided by Iain McDonald of Engage Scientific Solutions. The study was funded by Pfizer. Disclosure of Interests: Donna Cox Shareholder of: Pfizer Inc, Employee of: Pfizer Inc, Daniel Alvarez Shareholder of: Pfizer, Employee of: Pfizer, Amy Bock Shareholder of: Pfizer, Employee of: Pfizer, Carol Cronenberger Shareholder of: Pfizer, Employee of: Pfizer